Temporal variability in the growth-enhancing effects of different bacteria within the microbiome of the diatom Actinocyclus sp. - Le Reun, Nine; Bramucci, Anna; Ajani, Penelope; Khalil, Abeeha; Raina, Jean-Baptiste; Seymour, Justin R. (Frontiers in Microbiology, 2023)
Reciprocal metabolite exchanges between diatoms and bacteria can enhance the growth of both partners and therefore fundamentally influence aquatic ecosystem productivity. Here, we examined the growth-promoting capabilities of 15 different bacterial isolates from the bacterial community associated with the marine diatom Actinocyclus sp. and investigated the magnitude and timing of their effect on the growth of this diatom. In the presence of its microbiome, Actinocyclus sp. growth was significantly enhanced relative to axenic cultures.Co-growth with each of the 15 bacterial isolates examined here (seven Rhodobacteraceae, four Vibrionaceae, two Pseudoalteromonadaceae, one Oceanospirillaceae and one Alteromonadaceae) increased the growth of the diatom host, with four isolates inducing rates of growth that were similar to those delivered by the diatom's full microbiome. However, the timing and duration of this influence differed between the different bacteria tested. Indeed, one Rhodobacteraceae and one Alteromonadaceae enhanced Actinocyclus sp. cell numbers between days 0-6 after co-incubation, five other Rhodobacteraceae promoted diatom cell numbers the most between days 8-12, while four Vibrionaceae, one Oceanospirillaceae and one Rhodobacteraceae enhanced Actinocyclus sp. cell abundance between days 14-16. These results are indicative of a succession of the growth-enhancing effects delivered by diverse bacteria throughout the Actinocyclus sp. life cycle, which will likely deliver sustained growth benefits to the diatom when its full microbiome is present.